Acoustic propagation in realistic 3D nonlinear internal waves - Duncan, Alec; Shimizu, K.; Parnum, Iain; MacLeod, R.; Buchan, S. (2020)
Nonlinear internal waves are a feature of many continental margins, particularly those with large tidal ranges such as Australia's Northwest Shelf. This paper extends previous work on the effects of idealised nonlinear internal waves on acoustic propagation at mid-frequency sonar frequencies to the case of a realistic, fully three-dimensional, time evolving internal wave field. The internal wave field was modelled using MITgcm, which is a state of the art, three-dimensional, non-hydrostatic hydrodynamic model. Time evolving, three-dimensional sound velocity fields were calculated from the MITgcm temperature and salinity outputs and used as input to the Bellhop3D acoustic propagation model, which was used to calculate the variations in transmission loss that occurred as a nonlinear internal wave train crossed the acoustic transmission path. Results were broadly consistent with those obtained previously using the idealised internal wave train but predicted somewhat smaller changes in transmission loss between horizontally focussed and defocussed conditions of up to 18 dB compared to changes of up to 30 dB obtained with the idealised internal waves. Analysis of more events is required in order to test the robustness of this result.